ECO-FRIENDLY CONSUMERS IN THE FOURTH INDUSTRIAL REVOLUTION: ACADEMIC SOCIETY, GREEN CUSTOMERS, AND ECO LABELLING - Budiasih, Yanti (Muhammadiyah International Journal of Economics and Business, 2018)
This analytical descriptive research aims to find out the relationship between the investigated variables. These variables had been previously tested hence this study made several modifications. The   data  consisted  of   primary   data  and  involved   150   students   of  Ahmad   Dahlan   Economics School  as the  respondents.  The  research variables  were divided  into  exogenous  variables (i.e.,  eco  labeling,   eco  knowledge, green  product,   green  packaging  and   green  advertising)   and endogenous  variables (i.e.,  purchase  intention  and green  customer).  The  data analysis  technique was the Partial Least Square (PLS) by using SmartPls software. Based on the results of hypothesis testing, it can be concluded that: eco-knowledge has a significant negative influence on purchase intention; eco-knowledge has a significant negative influence on green customers; eco-labeling has a significant positive influence on purchase intention; eco-labeling has a significant negative influence on green customer; green product has a  significant positive influence on purchase intention; green product has a significant positive influence on green customer; green packaging has an insignificant influence on purchase intention; green packaging has an insignificant influence on green customer; green advertising has a significant negative influence on purchase intention; green advertising has a significant positive influence on green customer; and purchase intention has a significant positive influence on green customer.